Factors Associated with Community Perception of Public Safety Center (PSC) in Silinda District, Serdang Bedagai Regency - Saragih, Eriani Senaya; Barita Aritonang; Sri Melda Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
The Public Safety Center (PSC) serves as a rapid, precise, and careful response facility for communities in emergency situations, providing 24/7 services. This study aims to identify factors related to community perception of PSC in Silinda District, Serdang Bedagai Regency. Using a quantitative method with a cross-sectional design. The population in this study consists of all residents in Silinda District, Serdang Bedagai Regency, totaling 5,055 people. The sampling technique used in this study is purposive sampling. the study found that Education has the most significant influence on community perception of PSC, With P value = 0,000 and EXp(B) = 192,893. This indicates that individuals with higher education tend to have a more positive perception of PSC. The analysis concludes that Education and Knowledge are factors related to community perception of PSC in Silinda District. The conclusion is that public perception of the Public Safety Center (PSC) is influenced by several factors. There is no significant relationship between the age variable and public perception of the PSC. However, there is a significant relationship between the level of education and public knowledge and their perception of the PSC, indicating that the higher a person's education and knowledge, the more positive their perception of PSC services. Meanwhile, variables related to needs such as information, facilities and infrastructure, and healthcare personnel do not show a significant relationship with public perception. It is recommended to increase awareness and knowledge about PSC and its role in enhancing safety and security.